Sistem Informasi Pendataan Pelanggaran Peraturan Daerah Pada Satuan Polisi Pamong Praja Kota Padang - Putri, Nency Extise; Elizamiharti, Elizamiharti; Arman, Arman (JOSTECH: Journal of Science and Technology, 2021)
The Civil Service Police Unit (Satpol PP) of Padang City is a supporting element of the Padang City Government's task in securing and implementing City Government policies that are specific in the field of peace and public order. So many data on violations are handled and the manual data collection of violations results in not yet optimal management of data on violations of Regional Regulations (Perda), so we need an information system for collecting data on violations of regulations. The method of development in the preparation of this study in library research, field research, laboratory research and System Development Life Cycle (SDLC). The author's program implementation uses PHP programming language with MySQL Server database. With the implementation of the information system on collecting data on local violations in Padang City Satpol PP, it is hoped that it will simplify and speed up the management of regulations on local regulations, so that service to the community is better.Â